Status and promise of particle interferometry in heavy-ion collisions - Bekele, Selemon [UNESP]; Braghin, Fabio [UNESP]; Chajȩcki, Zbigniew [UNESP]; Chung, Paul [UNESP]; Cramer, John G. [UNESP]; Csörgo, Tamás [UNESP]; Eggers, Hans [UNESP]; Gavin, Sean [UNESP]; Grassi, Frédérique [UNESP]; Hama, Yogiro [UNESP]; Kisiel, Adam [UNESP]; Ko, Che-Ming [UNESP]; et al. (FapUNIFESP (SciELO), 2007)
After five years of running at RHIC, and on the eve of the LHC heavy-ion program, we highlight the status of femtoscopic measurements. We emphasize the role interferometry plays in addressing fundamental questions about the state of matter created in such collisions, and present an enumerated list of measurements, analyses and calculations that are needed to advance the field in the coming years.
Keywords: Particle-antiparticle correlations; Theoretical and experimental femtoscopy; Theoretical and experimental identical-particle correlations